Ιταλικός κινηματογραφικός νεορεαλισμός και ελληνική μεταπολεμική πεζογραφία: Νεορεαλιστική γραφή στο Άνθρωποι και σπίτια του Αντρέα Φραγκιά. - Φραγκούλη Νάντια Αυγερινός (Σύγκριση/Comparaison/Comparison, 2018)
The years 1951-1961 mark the reception of Italian neorealist cinema in Greece with the production of films influenced by neorealism and the discussion of the nature of neorealism by Greek film critics. The novel Anthropi ke spitia [Of Houses and Men] by Adreas Fragkias, published in 1955, four years after the first viewing of De Sica’s Bicycle Thief in Greece, shows significant similarities to the themes and style of the Italian neorealist cinema. Discussing unemployment as a crucial problem of post-war Greek society Anthropi ke spitia presents the life in a poor urban neighbourhood in a series of seemingly random episodes that B. Klaras in his review of the book called ‘cinematic tableaux’. Most importantly, however, it seems that Fragkias’ novel explores the boundaries and the style of realism in post-war literature in a way that resonates the aesthetic principles of the Italian neorealistic films.